Longitudes and attitudes : - Friedman, Thomas L. (Farrar, Strauss and Giroux, 2002)
Longitudes and Attitudes contains the columns Friedman has published about the most momentous news story of our time, as well as a diary of his experiences and reactions during this period of crisis. As the author writes, the book is "not meant to be a comprehensive study of September 11 and all the factors that went into it. Rather, my hope is that it will constitute a 'word album' that captures and preserves the raw, unpolished, emotional and analytical responses that illustrate how I, and others, felt as we tried to grapple with September and its aftermath, as they were unfolding.